(untitled) (Research, Society and Development, 2023)
Spiritual intelligence has assumed an ambivalence regarding its belonging in studies of human or philosophical intelligence. To answer this question, the present study aims to develop theoretical research called snowball on the two themes that support it, namely: spirituality and intelligence. The study intends to develop a theoretical element that contributes to the discussions around spiritual intelligence, especially about the translation of the term in the area of psychology and philosophy. In this context, how much spirituality concerns reductions to religious beliefs, theoretically, has assigned theoretical and empirical spaces of general or multiple assessments to intelligence, as well as hereditary or learned. In general, the theme in question is reflected in an approach to spiritual intelligence regarding the cognitive capacity inherent in all individuals, which needs external stimuli for its development. Keywords: Intelligence; Spiritual intelligence; Spirituality; Theory.